Pengaruh Komitmen Kerja Dan Kepuasan Kerja Terhadap Loyalitas Kerja Karyawan Unit Airport Security Pada PT. Angkasa Pura Indonesia Kantor Cabang Bandara Internasional Minangkabau - Yolanda Abdillah Putri; Henny Sulistianingsih (GLOBAL SCIENTS PUBLISHER, 2025)
This research is a quantitative research. This study aims to determine how the influence of work commitment and job satisfaction on the work loyalty of Airport Security unit employees at PT Angkasa Pura Indonesia Minangkabau International Airport Branch Office. The population in this study were Airport Security unit employees with a sample of 105 respondents. The sample collection technique used was saturated sampling technique. Data were obtained by conducting a questionnaire, then processed and tested using SPSS. From the research conducted, it is known that the results of hypothesis testing indicate that work commitment and job satisfaction have a significant effect on the work loyalty of Airport Security unit employees at PT Angkasa Pura Indonesia Minangkabau International Airport Branch Office. The results of the coefficient of determination show that the influence of work commitment and job satisfaction on work loyalty is 56.3%. while the remaining 43.7% is influenced by other variables outside this study.